Anti-racist art activities for kids : 30+ creative projects that celebrate diversity and inspire change - Birhanu, Abigail (Quarry, 2023)
"Anti-Racist Art Activities for Kids offers creative projects for kids ages 8-12 to inspire change within themselves, their community, and the larger world"--